Sacred Paper: Exploring the Materiality and Symbolism of Daluang in Balinese Hindu Rituals - Permadi, Tedi; Guzzini , Alva; Kurniasih, Euis (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
Balinese Hinduism provides a rich context for exploring the intersection of material culture and religious belief. This study aims to explore the dual roles of daluang (also known as walantaga) in Balinese Hindu rituals, functioning both as a ritual object and a sacred symbol. Utilizing ethnographic methods and textual analysis, the research draws from four Balinese Hindu lontar manuscripts, including Kakawin Ramayana, Wedana Pujastawa, Yajna Prakerti and Pujastawa Wedana. Data collection involved participant observation and interviews conducted with seven Hindu priests. Guided by Geertz’s interpretive framework, findings reveal that daluang serves not only as a material for crafting key ritual items but also as a vital medium for spiritual communication, embodying core cultural values and cosmological concepts within Balinese Hinduism. This study contributes to broader discussions on the role of material culture in sustaining intangible religious heritage and expression in contemporary Balinese society.
Keywords: Balinese Hinduism; daluang; interpretive approach; ritual; sacred symbol; walantaga